Health and Inequality - Owen O'Donnell; Eddy Van Doorslaer; Tom Van Ourti (Tinbergen Institute, 2013)
We examine the relationship between income and health with the purpose of establishing the extent to which the distribution of health in a population contributes to income inequality and is itself a product of that inequality. The evidence supports a significant and substantial impact of ill-health on income mainly operating through employment, although it is difficult to gauge the magnitude of the contribution this makes to income inequality. Variation in exposure to health risks early in life is a potentially important mechanism through which health may generate, and possibly sustain, economic inequality. If material advantage can be excercised within the domain of health, then economic inequality will generate health inequality. In high income countries, the evidence that income (wealth) does have a causal impact on health in adulthood is weak. But this may simply reflect the difficulty of identifying a relationship that, should it exist, is likely to emerge over the lifetime as poor material living conditions slowly take their toll on health. There is little credible evidence to support the claim that the economic inequality in society threatens the health of all its members, or that relative income is a determinant of health.
Keywords: D31; I14; J3; 330; income; wealth; health; inequality